The Characteristics of the Historical Floods from the Years 1974 and 1975 in the Bâsca Basin. - Lidia SĂLĂJAN; Daniela Elena GOGOAȘE NISTORAN (Aerul şi Apa: Componente ale Mediului, 2019)
The floods that took place in the Bâsca river basin over time had short and medium duration, the flooding generated by them having had significant consequences on social life, economic activities and environment. Short and medium duration floods generally occur during summer and last for a total of 2- 6 days. These are due to heavy rainfalls (100-300 mm), with high intensity (due to atmospheric instability, thermal conventions and cyclone formation over the Black Sea). The largest floods in the Bâsca river basin occurred in the years 1974, 1975, 1991 and 2005. In this study, the historical floods from June 1974 and July 1975 were analysed on the rivers: Bâsca Mare (Varlaam I hydrometric station), Bâsca Mică (Varlaam II hydrometric station) and Bâsca (the Bâsca Roziliei hydrometric station). In the generation of floods within this hydrographic basin, the geographic factors such as relief, geological formations and lithology, hydrography, vegetation, soil, climate and anthropic activity are of particular importance.